Expansão canavieira e seus efeitos na violência em Goianésia - ALVES, Glauco Leão Ferreira (2012)
In Goiás, the process of occupation of the territory still happens today. Livestock, rice, corn and soybeans that once moved over the cerrado, gradually transferring go area for cane sugar. The sugarcane expansion was influenced by increased demand for ethanol due to growth in sales of flex-fuel vehicles, especially in the last decade. Thus, there was an increase in cultivated area for sugar cane, showing a change in consumption of energy. The concern from various sectors of society is that in many regions, the sugar cane harvest is still done manually by pruning and many social and environmental problems are arising from this form of management, such as fires and poor working conditions. In Goianésia largest municipality of sugarcane Microregion of Ceres, violence has increased, mainly related to drug use in the years 2009 and 2010. There are reports of drug use to provide more force some workers to cut cane or to provide relief from stress as a result of one day of paid work for productivity.